Expression and Prognosis Analysis of SUMOylation Regulators in Oral Squamous Cell Carcinoma Based on High-Throughput Sequencing - Meng, Yutong; Li, Xiaozhi (Frontiers in Genetics, 2021)
Introduction: Oral squamous cell carcinoma (OSCC) originates from oral mucosal epithelial cells, accounting for more than 90% of oral cancers. The relationship between the expression and prognostic role of SUMOylation regulators in OSCC is rarely studied. Materials and methods: The expression and survival data of OSCC were derived from TCGA and GEO databases. Wilcoxon test was used to determine the differential expression of the SUMOylation regulators. A prognostic model based on SUMOylation regulator-related genes was constructed by Cox regression. Gene set enrichment analysis was applied to predict the potential biological functions that the genes might be involved in. Results: RANBP2 and SENP6 had the highest SNV frequency. 11 genes including PIAS3, RANBP2, USPL1, SENP6, SENP2, SENP5, SAE1, UBA2, PIAS4 UBE2I, and SENP3 were highly expressed in OSCC. The prognostic model based on 9 SUMOylation-regulated genes (TRIM37, UFM1, FUBP1, CCNT1, FXR1, HMG20A, RANBP3, SPATA5 and DDX23) had a strong ability to predict the prognosis of OSCC. Conclusion: This study might provide targets for prognostic evaluation and targeted therapy of patients with OSCC.